03.06 Mer-mediated efferocytosis tempers arthritis by preventing neutrophil littering in the joint. (1st March 2017) - Waterborg, Claire EJ; Beermann, Silke; Rothlin, Carla V; Koenders, Marije I; Bennink, Miranda B; van der Kraan, Peter M; van Lent, Peter LEM; van den Hoogen, Frank HJ; Lemke, Greg; van de Loo, Fons AJ
Abstract : Background: Rheumatoid arthritis is characterised by an inflammatory response in synovial joints, showing a predominant influx of neutrophils. These cells have a relative short life span and many of them undergo apoptosis. If they are not cleared, they undergo secondary necrosis and release their cell content which promotes inflammation. One receptor involved in the uptake of apoptotic cells, called efferocytosis, is the Mer tyrosine kinase receptor. In addition, Mer is involved in an anti-inflammatory natural feedback mechanism. One of the ligands for Mer is Protein S (Pros1). The local role of Mer during arthritis, however, has not been elucidated. Materials and methods: One day after the booster injection of collagen-induced arthritis in mice, a commercially available antibody against Mer was injected intravenously or an adenovirus overexpressing Pros1 was injected intra-articularly into the knee joints. Mice were euthanized at day 30 or 36, respectively. The KRN serum transfer model was induced by two injections of arthritic K/BxN serum on day 0 and 2 in either Mer-deficient mice or in wild type mice that overexpress Pros1 in their knee joints. Mice were euthanized at day 7 or day 14, respectively. From all mice, serum was taken for cytokine profiling and knee joints were isolated for histology and immunohistochemistry. Results: Overexpression of the Mer ligand Pros1 resulted in reduced production of inflammatory mediators by the synovial cells of arthritic mice in addition to diminished joint pathology. Conversely, inhibiting Mer-mediated efferocytosis by either antibodies or Mertk ablation resulted in aggravation of arthritis, exhibited by increased inflammation and tissue destruction. Additionally, these mice had an increased percentage of active Caspase-3 positive cells in their joints, a marker for apoptotic cells, and higher serum levels of IL-16C, a cytokine released by secondary necrotic neutrophils. On the contrary, Pros1 overexpression led to reduced numbers of apoptotic and secondary necrotic neutrophils. Conclusions: To conclude, activation of Mer plays a unique, protective role in controlling the severity and resolution of inflammation in experimental arthritis. Our data suggest that promoting Mer-mediated uptake of apoptotic cells in the arthritic joint might be therapeutically beneficial.